THE IMPLEMENTATION OF ENGLISH TEACHERS’ AUTHENTIC ASSESSMENT IN JUNIOR HIGH SCHOOLS - Amirul, Bani; Chairunnissa, Chairunnissa (VISION, 2024)
A descriptive study was performed at SMP Negeri 1 Kotapinang to measure the perceived ability of English instructors regarding authentic assessment. The research process employed surveys, interview guides, and observation. Both interactive and descriptive models were employed to analyse the data. The assessed expertise of the English teachers at SMP Negeri 1 Kotapinang regarding the implementation of authentic assessment was commendable. Educators utilised portfolios, projects, peer evaluations, performance assessments, and observations as authentic assessment methods. The perceived comprehension and implementation of project evaluation and peer/self-assessment reveal disparities. Authentic assessment is executed differently in online education than in traditional classroom instruction. The educators implemented specific modifications, including assessing the students' attitudes in the classroom. The observation of attitudes in online learning was adjusted based on students' engagement in the course and their assignment responsibilities.